Fundamental concepts of language teaching - Stern, H. H. (Oxford University Press, 1997)
The book is divided into six parts: 1) Clearing the ground, sets the tone for the whole book in its careful definition of terms and its view of current issues. 2) Historical perspectives, provides a survey of language teaching trends from 1880 to the present day. 3) Concepts of language, deals with trends in linguistic theory and their relationship to language teaching. 4) Concepts of society, traces the development of sociology and anthropology as academic disciplines, and considers the bearing each has on the study of language and language learning. 5) Concepts of language learning, aims to draw up a theoretical base for language teaching which relates both to the individual learner and to the language learning process as a whole. 6) Concepts of language teaching, deals with the study of education and its relevance to language teaching